Inovasi Produk UMKM Opak Singkong Sebagai Upaya Peningkatan Sektor Perekonomian Warga Desa Ciomas - Muhammad Angga Anggriawan; Evi Dora Sembiring; Deti Susilawati; Khaerul Anwar; Alvin Prasetio; Alpinah Damayanti (Gapenas Publisher, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) exists as a solution to the economic system that makes it easier for people to be ready to compete in market conditions. With the aim of expanding employment opportunities, equal distribution of income, alleviating poverty, creating village entrepreneurs, the role of Micro, Small and Medium Enterprises (MSMEs) is very important in society. The aim of the service is to provide assistance in the utilization and development of MSMEs as an effort to increase sales and people's buying interest. The method of implementing service is in 3 (three) stages, namely the preparation stage, implementation stage and evaluation stage. Based on the results of the implementation of activities, it can be seen that it is hoped that assistance in the utilization and development of MSMEs as an effort to improve the economic sector of the Mulyajaya Village community can help the community, government, researchers and academics in planning the latest programs that will make a big contribution to the community's economy. Therefore, Micro, Small and Medium Enterprises (MSMEs) have an important role in the local regional economy in driving the economic activities of village communities. In the context of implementing, planning, empowering and developing Micro, Small and Medium Enterprises (MSMEs) regulations from the government are needed to provide opportunities for the development of MSMEs